2004
DOI: 10.1128/iai.72.6.3674-3679.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Cryptococcus neoformans Glucuronoxylomannan Inhibits the Release of Capsular Antigen

Abstract: Cryptococcus neoformans releases capsular polysaccharide in the supernatant of liquid cultures and in tissues. Significantly less glucuronoxylomannan (GXM) was released by C. neoformans in the presence of capsule-binding monoclonal antibody (MAb). MAb-mediated inhibition of GXM release may be another mechanism by which humoral immunity can mediate protection against this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
2
38
1
1
Order By: Relevance
“…A higher 18B7 concentration of 50 g/ml paradoxically decreased levels of GXM release, likely due to the cross-linking and aggregation of fungal cells, which was visualized by india ink stain, effectively locking the capsule in place. This phenomenon has been described previously with live C. neoformans and concentrations of 18B7 50 g/ml and higher (49). At these higher antibody concentrations, the reduction in GXM released due to cross-linking overwhelms the amount of GXM hydrolyzed by 18B7.…”
Section: Discussionmentioning
confidence: 58%
“…A higher 18B7 concentration of 50 g/ml paradoxically decreased levels of GXM release, likely due to the cross-linking and aggregation of fungal cells, which was visualized by india ink stain, effectively locking the capsule in place. This phenomenon has been described previously with live C. neoformans and concentrations of 18B7 50 g/ml and higher (49). At these higher antibody concentrations, the reduction in GXM released due to cross-linking overwhelms the amount of GXM hydrolyzed by 18B7.…”
Section: Discussionmentioning
confidence: 58%
“…The results were consistent with the upregulation of the entire fatty acid synthesis pathway seen in the microarray when H99 was bound by mAb 18B7. Given prior observations that mAb 18B7 inhibits polysaccharide shedding in vitro (8) and biofilm formation (9), together with recent evidence that the major component of the capsule, GXM (27), and other major virulence factors (28), are exported to the cell exterior in lipid vesicles, our data suggest an association between lipid metabolism and capsule production/shedding, which appears to be reflected in the metabolic changes observed. Additionally, it is possible that changes in lipid metabolism are seen because mAb 18B7 binds very close to the cell wall, and this binding may somehow perturb membrane lipids that in turn produce regulatory changes in lipid metabolism (29).…”
Section: Figurementioning
confidence: 91%
“…For the human pathogenic fungus C. neoformans, Ab-mediated protection is associated with interference of polysaccharide release and biofilm formation (8,9). For example, the IgG1 mAb 18B7 and IgM mAb 12A1 each inhibit biofilm formation and polysaccharide release, while the IgM mAb 13F1 has no effect on either phenomenon (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to the polysaccharide capsule can enhance survival (10), promote phagocytosis (29), affect complement activation (19), alter cytokine expression in vivo (11), clear serum polysaccharide antigen (14), enhance antigen presentation (38), and modulate expression of immunologically important molecules (26). In addition, we recently demonstrated that specific antibody could inhibit GXM release from cells, possibly by cross-linking GXM molecules in the capsule (22). Since C. neoformans can form biofilms on medical devices that presumably contain polysaccharide components (41), this finding raised the intriguing possibility that antibody to GXM would also interfere with cryptococcal biofilm formation.…”
mentioning
confidence: 99%